The effect of exercise-induced hypoxemia on blood redox status in well-trained rowers - Kyparos, A.; Riganas, C.; Nikolaidis, M. G.; Sampanis, M.; Koskolou, M. D.; Grivas, G. V.; Kouretas, D.; Vrabas, I. S. (European Journal of Applied Physiology, 2012)
Exercise-induced arterial hypoxemia (EIAH), characterized by decline in arterial oxyhemoglobin saturation (SaO(2)), is a common phenomenon in endurance athletes. Acute intensive exercise is associated with the generation of reactive species that may result in redox status disturbances and oxidation of cell macromolecules. The purpose of the present study was to investigate whether EIAH augments oxidative stress as determined in blood plasma and erythrocytes in well-trained male rowers after a 2,000-m rowing ergometer race. Initially, athletes were assigned into either the normoxemic (n = 9, SaO(2) >92%, [Formula: see text]: 62.0 ± 1.9 ml/kg.min) or hypoxemic (n = 12, SaO(2) <92%, [Formula: see text]: 60.5 ± 2.2 ml kg(-1 )min(-1), mean ± SEM) group, following an incremental [Formula: see text] test on a wind resistance braked rowing ergometer. On a separate day the rowers performed a 2,000-m all-out effort on the same rowing ergometer. Following an overnight fast, blood samples were drawn from an antecubital vein before and immediately after the termination of the 2,000-m all-out effort and analyzed for selective oxidative stress markers. In both the normoxemic (SaO(2): 94.1 ± 0.9%) and hypoxemic (SaO(2): 88.6 ± 2.4%) rowers similar and significant exercise increase in serum thiobarbituric acid-reactive substances, protein carbonyls, catalase and total antioxidant capacity concentration were observed post-2,000 m all-out effort. Exercise significantly increased the oxidized glutathione concentration and decreased the ratio of reduced (GSH)-to-oxidized (GSSG) glutathione in the normoxemic group only, whereas the reduced form of glutathione remained unaffected in either groups. The increased oxidation of GSH to GSSG in erythrocytes of normoxemic individuals suggest that erythrocyte redox status may be affected by the oxygen saturation degree of hemoglobin. Our findings indicate that exercise-induced hypoxemia did not further affect the increased blood oxidative damage of lipids and proteins observed after a 2,000-m rowing ergometer race in highly-trained male rowers. The present data do not support any potential link between exercise-induced hypoxemia, oxidative stress increase and exercise performance.